Wage Differences Between Men and Women in Austria: Evidence from 1983 and 1997 - René Böheim; Helmut Hofer; Christine Zulehner (Institute for the Study of Labor (IZA), 2005)
In most OECD countries the wage gap between men and women has declined during the past two decades. Developments of the last 20 years, e.g. increased labour market attachment of women, changes in the bargaining structure, and the introduction of equal pay laws, may have reduced the gender wage gap. We investigate the extent, persistence, and socio-economic determinants of the gender wage gap in Austria, for the years 1983 and 1997. Using wage decomposition techniques, we find that the average gender wage gap was almost as high in 1997 as it was in 1983. Not accounting for differences, the gender wage gap dropped from 25.5 to 23.3 per cent. Taking observable differences between men and women into account, we estimate that the mean gender wage gap which cannot be explained, i.e. discrimination against women, dropped from 18 to 15.5 per cent of men?s wages. The drop in discrimination is the main reason for the narrowing of the gender wage gap.
Keywords: J71; J31; 330; wage differentials; wage inequality; decomposition